Some recurrent Issues in Contemporary Society in the Novels of Birendra Kumar Bhattacharya and Indira Goswami (International Journal of Psychosocial Rehabilitation, 2020)
The fiction from Northeast India represents the issues of history, identity, migration, culture, and tradition. This region is enriched with distinct culture, tradition, customs, rituals, and beliefs. It is geographically, linguistically, ethnically, and culturally different from the mainland India. Though the novelists write in English, they are unique. Novelists from this region delineate a beautiful geographical location and distinct culture and tradition that is rich in diversity. Political unrest, ethnic conflict, violence, insurgency, kidnapping, and extortion form some of the recurrent themes in Northeast Indian English fiction. All these have created an interesting area of literary study, which is an emerging literary field. Literature from Northeast India represents identity crises from the perspectives of regional history and gender biasness. It blends personal, family, regional, and national issues in order to show the truth of history and identity in different sections of society. Such issues are discussed in select novels and novelists of the said topic.Birendra Kumar Bhattacharya’s Love in the Time of Insurgency (1960) and Mrityunjay (1970) explore representation of regional history in blending regional and national issues. In Indira Goswami's The Man From Chennai (2005) and The Moth-Eaten Howdah of the Tusker (1988), examine how women’s identities are eroded and silenced because of patriarchy and gender discrimination in society.